Tunable Fano Resonance and Enhanced Sensing in Terahertz Metamaterial - Wang, Yun; Jia, Shengyao; Qin, Jianyuan (Frontiers in Physics, 2021)
Fano resonances in metamaterial are important due to their low loss subradiant behavior that allows excitation of high quality (Q) factor resonances extending from the microwave to the optical bands. High Q Fano resonances have recently showed their great potential in the areas of modulation, filtering, and sensing. However, the Fano resonances in a metamaterial system arise from the interaction of all resonators (unit cells) that form the metamaterial structure, which limit the tunability of the resonances. Besides, sensing trace analytes using Fano resonances are still challenging. Here, we demonstrate the excitation of Fano resonances in metamaterial consisting of a period array of two concentric double-split-ring resonators with symmetry breaking. The tunability and the sensing of Fano resonances are both detailedly studied. Introducing position asymmetry in the metamaterial leads to one Fano resonance located at 0.50 THz, while introducing gaps asymmetry results in two Fano resonances located at 0.35 THz and 0.50 THz. The all three Fano resonances appear due to the symmetry breaking of the resonators, and they can be easily tuned by varying the asymmetry deviations. The Q factor and figure of merit (FoM) of Fano resonances in asymmetry metamaterial with different asymmetry deviations are calculated and analyzed. The Fano resonances having the highest FoM are used for the sensing of analytes at different refractive indices, and the Fano resonance performing the best in refractive index sensing is further applied to detect the analyte thickness. The results demonstrate that the tunable Fano resonances show tremendous potential in sensing applications, offering an approach to engineering highly sensitive sensor devices.